Encryption in a Windows Environment EFS File, 802.1x wireless, IPSec transport, and S/MIME exchange - Morimoto, Rand (Sams Pub., 2006)
With the current business, government, and institutional focus on security, organizations are scrambling to make their networks more secure. Although encryption is nothing new to Windows, recent advances in Microsoft ® Windows 2003 and Microsoft ® Windows XP have drastically simplified the support of encryption technologies in Windows environments. Delivered in Adobe PDF format for quick and easy access, Encryption in a Windows Environment: EFS File, 802.1x Wireless, IPSec Transport, and S/MIME Exchange, 1/e covers the installation and operation of EFS file encryption, IPSec communications encryption, 802.1x wireless encryption, L2TP mobile encryption, as well as the auto-enrollment of certificates that drastically simplifies the administration of encrypted communications. The encryption technologies addressed in this digital Short Cut are included in all copies of Microsoft ® Windows 2003 and Microsoft ® Windows XP. Table of Contents Section 1 What This Short Cut Will Cover Section 2 Security the Manual Way Section 3 Installing a Windows Certificate of Authority Server Section 4 Implementing Encrypted File System (EFS) Section 5 Implementing IPSec-Encrypted Transport Communications Section 6 Implementing 802.1x Wireless Encryption Section 7 Implementing Secured Email Communications with Exchange 2003 Section 8 Summary and Other Resources.
Keywords: Microsoft Windows (Computer file); Computer security; Data encryption (Computer science); Sécurité informatique; Chiffrement (Informatique)